Estudo do linfonodo sentinela em câncer de mama no estado do Pará- Período: 2001/2005 - COIMBRA, Alexandra Penha (2022)
The standard procedure in breast cancer patients used to be a radical mastectomy with axillary lymph node dissection. As time went by, more conservative methods were studied without risks to leave residual illness. Therefore it follows that new methods have been developed for staging and treatment of the axilla as well. Axillary lymph node dissection comes with a substantial morbidity (lymphedema, sensory loss and pain). Although these complaints are usually not severe, the incidence is high. In this context, the search of the sentinel lymph node (SLN), brought new perspectives in the axillary boarding, in this type of cancer. The SLN is defined as the node that receives afferent lymphatic drainage directly from a primary tumor. According to searches in this area, the axillary lymph node dissection should be accomplished only when the SLN is compromised with metastasis cell. Objectives: The present study evaluates the effectiveness of search of sentinel lymph node in the breast cancer. At that way, only those patients who have metastasis axillary will be submitted to axillary dissection, reducing the morbidity. Methods: It was included in this study 86 patients with breast cancer histologically confirmed, who were submitted to the lymphoscintigraphy to look for SLN, in the period of 2001 and 2005. Results: It was shown that axillary dissection was unnecessary in patients with negative SLN. Conclusion: The search of the LS presents high negative predictive value, which contributes to reduce the morbidity in patients with breast cancer.